Comparative physical fitness profiles of female long-distance and sprint swimmers at Petrokima Gresik Club: A descriptive study - Kartika Jeaniar Fajar Nur Rahma (Sport, Exercise, and Injury, 2025)
Background: Physical condition is a fundamental factor that affects swimmers' performance in developing techniques, tactics, and competition strategies, especially for swimmers specializing in different distances, such as sprinters and long-distance swimmers. Objectives: This study aims to analyze the dominant physical profiles of female sprinters and long-distance swimmers, providing evaluation material for coaches to develop more targeted training programs. Methods: The study employed a quantitative descriptive design, utilizing a survey and test approach. The research subjects consisted of 20 female swimmers from the Petrokimia Gresik Club who were selected purposively, including 10 sprinters and 10 long-distance swimmers. Data collection was conducted in 2024 through push-up tests (measuring arm muscle strength), sit-ups (assessing abdominal muscle strength), vertical jump (evaluating leg muscle explosive power), and multistage fitness tests (testing aerobic endurance). Raw scores were converted into t-scores and then categorized using the Norm Reference Scale (NRS). Data analysis was performed descriptively using means, standard deviations, and percentages. This study has obtained ethical approval from the relevant ethics committee. Results: The analysis results show that in the sprinter group, 4 out of 10 athletes (40%) were in the "fair" physical condition category, while in the long-distance group, 5 out of 10 athletes (50%) were also in this category. In general, the components of arm muscle strength, abdominal muscle strength, leg muscle power, and aerobic endurance in both groups showed a relatively balanced distribution with a predominance of the adequate category. Conclusions: The physical condition of female sprinters and long-distance swimmers from the Petrokimia Gresik Club was at a relatively balanced level, with a predominance of the adequate category. These findings serve as a basis for evaluating and adjusting training programs according to the characteristics of specific swimming specializations.